The global floriculture industry : shifting directions, new trends, and future prospects - Hakeem, Khalid Rehman (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2021)
"The Global Floriculture Industry: Shifting Directions, New Trends, and Future Prospects presents some of the latest research trends and areas of improvement to benefit the floriculture industry and to understand future directions and prospects. The research addresses the global floriculture industry's shift from traditional to a commercial focus. The global economy has spurred entrepreneurs to focus on the growing trend of export-oriented floriculture under controlled climatic conditions. The volume also looks at the role of plants in stabilizing the environment and the use of scientific knowledge through research that has changed the perspective of modern floriculture. This new book is a valuable compilation of the latest research work and areas of improvement in floriculture today. Key features: Provides an overview of the global floriculture industry, looks at the role of bulbous ornamentals, considers enhancing consumer-preferred traits in floriculture crops through genetic manipulation, explores using ornamental plants to stabilize the environment."--
The Global Floriculture Industry: Status and Future Prospects / Ismail Abiola Adebayo, Victoria Kaneng Pam, Hasni Arsad, and Mohammad Razip Samian -- Bulbous Ornamentals: Role and Scope in the Floriculture Industry / Fahima Gul, Waseem Shahri, and Inayatullah Tahir -- Micropropagation of Tulipa Species / Musadiq Hussain Bhat, Mufida Fayaz, Amit Kumar, Mudasir Fayaz, Rafeeq Ahmad Najar, Musfirah Anjum, and Ashok Kumar Jain -- Ornamental Plants: Some Molecular Aspects / Waseem Shahri, Fahima Gul, and Inayatullah Tahir -- An Overview of the Pharmacological Properties and Potential Applications of Lavender and Cumin / Muneeb U. Rehman, Sheikh Bilal Ahmad, Aazima Shah, Bismah Kashani, Anas Ahmad, Rakesh Mishra, Rehan Khan, Shahzada Mudasir Rashid, Rayeesa Ali, and Saiema Rasool -- Enhancing Consumer Traits in Floriculture Crops Through Genetic Manipulation for Production of Skin Medico-Cosmetics / Sheikh Umar Ahmad -- Caragana: An Important Ornamental Plant in Stabilizing the Environment / Muhammad Waseem, and Md. Mahadi Hasan.
OCLC-licensed vendor bibliographic record.
Keywords: Cut flower industry; Ornamental plant industry; Floriculture; SCIENCE / General; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Horticulture